Pseudophacopteron longicaudatum (Hemiptera) induces intralaminar leaf galls on Aspidosperma tomentosum (Apocynaceae): a qualitative and quantitative structural overview - OLIVEIRA, DENIS C. DE; MARTINI, VITOR C.; MOREIRA, ANA SILVIA F.P.; FUZARO, LEANDRO; GONÇALVES, LETÍCIA A. (Anais da Academia Brasileira de Ciências, 2020)
The structural complexity of galls depends on species-specific interaction driven by the galling taxa. However, the host plant and environment stressors can impose limits on gall developmental patterns and impact the establishment of gall morphology. Herein, we employed qualitative and quantitative approaches in order to elucidate how cell divisions, elongation patterns, and tissue organization are determinant for the development of intralaminar gall morphology induced by Pseudophacopteron longicaudatum Malenovský, Burckhardt, Queiroz, Isaias & Oliveira (Hemiptera: Psylloidea: Phacopteronidae) on leaves of Aspidosperma tomentosum Mart. (Apocynaceae). In addition, we aimed to determine which anatomical process can discriminate the stages of gall development, plus, examine the histochemical and cytological profiles of the galls. The differentiated structures, mainly abaxial epidermis and spongy parenchyma, are associated with gall closure, with hyperplastic events concentrated in the young phase of the galls. Thus, epidermis and spongy parenchyma hypertrophy and are responsible for the determination of the nymphal chamber formation and gall shape. The mature galls do not differentiate into a typical nutritive cells and do not develop a histochemical gradient in their tissues. The cytological features of galls such as plastoglobules and multivesicular bodies are related to ROS scavenging mechanisms due the high oxidative stress.The structural complexity of galls depends on species-specific interaction driven by the galling taxa. However, the host plant and environment stressors can impose limits on gall developmental patterns and impact the establishment of gall morphology. Herein, we employed qualitative and quantitative approaches in order to elucidate how cell divisions, elongation patterns, and tissue organization are determinant for the development of intralaminar gall morphology induced by Pseudophacopteron longicaudatum Malenovský, Burckhardt, Queiroz, Isaias & Oliveira (Hemiptera: Psylloidea: Phacopteronidae) on leaves of Aspidosperma tomentosum Mart. (Apocynaceae). In addition, we aimed to determine which anatomical process can discriminate the stages of gall development, plus, examine the histochemical and cytological profiles of the galls. The differentiated structures, mainly abaxial epidermis and spongy parenchyma, are associated with gall closure, with hyperplastic events concentrated in the young phase of the galls. Thus, epidermis and spongy parenchyma hypertrophy and are responsible for the determination of the nymphal chamber formation and gall shape. The mature galls do not differentiate into a typical nutritive cells and do not develop a histochemical gradient in their tissues. The cytological features of galls such as plastoglobules and multivesicular bodies are related to ROS scavenging mechanisms due the high oxidative stress.